Analysis of Student Misconceptions Using Five-Tier Diagnostic Test on Reaction Rate Material - Chatrine; Elfrida Ginting (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
Correct conceptual understanding is the basis for learning chemistry, including reaction rate material. This material is often considered challenging because of its abstract nature, which causes misconceptions in understanding reaction rate material and its application. This study examines students' misconceptions on reaction rate material by grade XI IPA students of SMAN 5 Medan. The method used is descriptive with a quantitative approach, including purposive sampling, tests, and interviews. Data analysis techniques include validation analysis by expert validators, quantitative analysis, and misconception analysis. Small-scale trials were conducted to test the validity and reliability of the instrument. Large-scale trials were conducted to assess students' misconceptions and identify sources of misconceptions from small-scale trials. Overall, the percentage of students' conceptual understanding levels in each category includes 51% of students having good understanding (SU), 31% having partial understanding (PU), 9% having poor understanding (NU), and 9% having misconceptions (MC), where the misconceptions that occur in students are in the low category, the same as the misconceptions for each reaction rate sub-material which is also in the low category. Item 21 has the highest misconception (20%), while items 1 and 22 have the lowest misconception (3%). Based on the source, the misconception category from personal thinking (MC-PT) has the highest misconception (44%), while the misconception category from books (MC-B) has the lowest misconception (11%). This study recommends exploring misconceptions in other materials.